Dioxin Inhibition of Swim Bladder Development in Zebrafish: Is it Secondary to Heart Failure? - Yue, Monica S. (Aquat Toxicol, 2015)
The swim bladder is a gas-filled organ that is used for regulating buoyancy and is essential for survival in most teleost species. In zebrafish, swim bladder development begins during embryogenesis and inflation occurs within 5 days post fertilization (dpf). Embryos exposed to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) before 96 hours post fertilization (hpf) developed swim bladders normally until the growth/elongation phase, at which point growth was arrested. It is known that TCDD exposure causes heart malformations that lead to heart failure in zebrafish larvae, and that blood circulation is a key factor in normal development of the swim bladder. The adverse effects of TCDD exposure on the heart occur during the same period of time that swim bladder development and growth occurs. Based on this coincident timing, and the dependence of swim bladder development on proper circulatory development, we hypothesized that the adverse effects of TCDD on swim bladder development were secondary to heart failure. We compared swim bladder development in TCDD-exposed embryos to: (1) silent heart morphants, which lack cardiac contractility, and (2) transiently transgenic cmlc2:caAHR-2AtRFP embryos, which mimic TCDD-induced heart failure via heart-specific, constitutive activation of AHR signaling. Both of these treatment groups, which were not exposed to TCDD, developed hypoplastic swim bladders of comparable size and morphology to those found in TCDD-exposed embryos. Furthermore, in all treatment groups swim bladder development was arrested during the growth/elongation phase. Together, these findings support a potential role for heart failure in the inhibition of swim bladder development caused by TCDD.